2003
DOI: 10.1348/000709903322275885
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles: Self‐reports versus thinking‐aloud measures

Abstract: Learning style theory was confirmed by results on the study process measures. The assessment of learning styles through self-report instruments such as the ILS, however, should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 15 publications
3
80
0
12
Order By: Relevance
“…In terms of the appropriateness of using self-report questionnaires, the present study corroborated previous research demonstrating that self-report surveys diverge from other measures of SRL� a �nding that is consistent with the SRL assessment literature showing that what students say that they do (self-report questionnaires) is oen not what they actually do [55,56]. is measurement characteristic can be problematic or advantageous to researchers or interventionists, depending on their research goals and objectives.…”
Section: Patterns Of Srl During Srep: Implications and Futuresupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of the appropriateness of using self-report questionnaires, the present study corroborated previous research demonstrating that self-report surveys diverge from other measures of SRL� a �nding that is consistent with the SRL assessment literature showing that what students say that they do (self-report questionnaires) is oen not what they actually do [55,56]. is measurement characteristic can be problematic or advantageous to researchers or interventionists, depending on their research goals and objectives.…”
Section: Patterns Of Srl During Srep: Implications and Futuresupporting
confidence: 87%
“…at is, despite evidence for shis in his strategic behaviors as noted previously, Vince did not perceive that he used strategies more frequently nor did his teacher report that he was more strategic during classroom activities. is lack of convergence may suggest that students may have difficulty accurately reporting their strategic behaviors, a premise consistent with prior research [55,56] or that self-report questionnaires may oen lack the sensitivity needed to capture speci�c shis in students' use of cognitive or regulatory strategies.…”
Section: Srep and Biology Exam Performancementioning
confidence: 71%
“…Previous studies examining this type of relationship using Vermunt's ILS 12 have shown conflicting results. For example, Veenman et al 19 found a nonsignificant relationship between learning styles and grade point average (GPA), while Boyle et al 13 found a significant relationship between the 2 factors. A more detailed analysis which excludes the scores of those (few) pharmacy students who have a prior degree and utilizes a standardized form of performance outcome (such as multiple-choice examination or essay style) for all year groups would perhaps be a more valid approach to this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While one study 13 found a significant relationship between productive approaches to learning and academic performance in a group of 273 second-and fourth-year social sciences students, other studies have found no such relationship. 18,19 Recent Australian research has shown that the process of undertaking final-year high school examinations can be counterproductive to fostering deep learning strategies or intrinsic interest and mastery of subject areas. [20][21][22] This body of work also found clear differences in these processes according to gender and subject area.…”
Section: Introductionmentioning
confidence: 99%
“…Although self-report scales continue to be the most frequently used measure by both researchers and practitioners, there has been some debate in the literature regarding whether selfreport measures are capable of measuring self-regulation in a valid way [39][40][41][42]. However, before one can support or refute the use of these measures, one first needs to clarify what is meant by term self-report.…”
Section: Types Of Self-regulation Assessmentmentioning
confidence: 99%